Adapting and validating informatics competencies for senior nurse leaders in the Canadian context: Results of a Delphi study. (September 2019) - Strudwick, Gillian; Nagle, Lynn M.; Morgan, Alicia; Kennedy, Margaret Ann; Currie, Leanne M.; Lo, Brian; White, Peggy
Highlights: Nurse leaders play an important role in the acquisition, implementation and optimization of health information technology. Currently senior nurse leaders may not be properly equipped to effectively participate in health informatics initiatives. A novel set of informatics competencies specific to nurse leaders in Canada have been identified. These initial competencies are being used as a starting point for similar studies in at least one other country. Abstract: Background: Nurse leaders in senior leadership positions in various parts of the world can play an important role in the acquisition, implementation and use of health information technologies. To date, international research related to nurse leader informatics competencies has been carried out in specific healthcare delivery contexts with very specific health information technology environments. In this body of literature, the definition of a 'nurse leader' has not been clearly defined. As a result, it is challenging for senior nurse leaders in leadership and management positions in other countries to apply this research to their unique contexts. Purpose: The objective of this study was to obtain consensus on the informatics competencies of priority to senior Canadian nurse leaders. The goal of completing this work was to adapt and validate a set of nurse leader informatics competencies to be endorsed and supported nationally. Methods: This study used a modified Delphi technique with a panel of nurse leaders with significant informatics knowledge from across Canada. Three rounds of information gathering were completed electronically. In Round 1, participants were provided a series of 26 potential competency statements obtained from a review of the literature; they were asked to comment on the clarity and wording of each statement. Two statements were eliminated after Round 1 due to redundancy. In Rounds 2 and 3, participants rated the remaining competency statements on a 7-point Likert scale for relative priority to nurse leaders. Results: A total of 25, 24 and 23 participants completed the survey in Rounds 1, 2 and 3 respectively. Consensus was achieved at the end of Round 3 with the inclusion of 24 competency statements. All of the statements had a mean of 5 or greater on a 7-point Likert scale (1=low priority and 7=high priority). Conclusions: The study participants agreed upon 24 informatics competency statements of priority to Canadian nurse leaders. These competencies will be presented to senior national nursing leaders and nursing informatics organizations for endorsement. Inspired by work completed in the United States, the authors plan to develop a self-assessment instrument for use by Canadian nurse leaders using the identified competency statements. Future anticipated work includes identifying and creating resources for nurse leaders to develop these important informatics competencies.